Rapid painless diagnosis of viral respiratory infection. Issue 5 (1st May 2002) - Ipp, M; Carson, S; Petric, M; Parkin, P C
Abstract : The concordance of nasal compared with nasopharyngeal swabs was assessed for the diagnosis of respiratory viral infections, and the degree of discomfort associated with each procedure was compared. The use of nasal swabs was shown to be as accurate but significantly less painful than nasopharyngeal swabs for virus diagnosis.